Air pollution and hospital admissions and deaths due to respiratory infections in megacity of Tehran: A time series analysis - Zahra Namvar (Tehran University of Medical Sciences, 2021)
Introduction: Air pollution is one of the main causes for the significant increase of respiratory infections in Tehran. In the present study, we investigated the associations between short-term exposure to ambient air pollutants with the hospital admissions and deaths.